A characterization and validation of the pyrogenic models and thermotric methids used for pharmacognostic evaluation of antipyretic medicine - Dangarembizi, Rachael (My University, 2018)
The development of safe and effective antipyretic and anti-inflammatory drugs remains an important focus of the pharmacological industry. Despite reports that rectal thermometry causes stress-induced hyperthermia in rodents, it remains the most commonly used method for measuring core body temperature during antipyretic drug-testing. The impact of the stressinduced hyperthermia on the accuracy and reliability of thermal responses reported in pharmacological studies investigating the efficacy of antipyretic drugs remains unclear. Additionally, the sickness response to Brewer’s yeast, the pyrogen recommended for inducing fever during antipyretic testing, remains largely uncharacterised and its mechanisms unknown. I used intra-abdominally implanted temperature-sensitive radiotelemeters to measure changes in the abdominal temperature of both normothermic and febrile rats injected with Brewer’s yeast, and exposed to rectal temperature measurement at hourly intervals for five hours. My results show that rectal temperature measurement is associated with a reproducible, nondecremental rise in abdominal temperature (0.6 - 0.8 °C) in normothermic rats. The hyperthermia was muted in febrile rats and was not blunted by the common habituation procedure. A comparison of temperatures measured using rectal thermometry with those measured using biotelemetry showed that rectal temperatures recorded using a thermocouple probe could be up to 0.5 °C lower or 0.7 °C greater than abdominal temperatures recorded using an abdominally implanted telemeter. The differences in thermal responses exhibited by normothermic vs febrile rats, coupled with the under- or overestimation of core body temperatures when one uses thermocouple probes supports my hypothesis that the procedure of rectal thermometry may affect the accuracy of thermal responses observed during antipyretic drug-testing. Having examined the methods used for temperature measurement, my second objective was to characterise the sickness response to the recommended and commonly used pyrogen for antipyretic screening; Saccharomyces cerevisiae (Brewer’s yeast). I measured the change in abdominal temperature, nocturnal activity, food intake and body mass gain in male Sprague Dawley rats injected subcutaneously with one of three doses of Brewer’s yeast (0.4, 0.2 and 4 g/kg). I further characterised the spatiotemporal activation of inflammatory mediators in the periphery (tumor necrosis factor alpha and interleukin (IL)-6) and in the brain (nuclear factor (NF) for interleukin 6, NF-kB, cyclooxygenase-2 (COX-2) and the signal transducer and activator of transcription (STAT)-3 in the vascular organ of the lamina terminalis (OVLT). Lastly, I measured the expression of hypothalamic inflammatory genes including: cytokines (IL-1b, IL-6, TNF-a), enzymes (COX-2 and microsomal prostaglandin synthase (mPGES)) and regulators of transcription factors (NF-kB inhibitor alpha (IkBa) and suppressor of cytokine signalling 3 (SOCS3)). My results show that Brewer’s yeast dose-dependently induces fever, lethargy, anorexia and body mass stunting. However, the sickness response to the high dose of Brewer’s yeast; the dose commonly used during antipyretic screening, was associated with an initial short-lived hypothermia, lengthy fevers, excessive peripheral and central inflammation and the development of an abscess. My last objective was to investigate if zymosan, a cell wall moiety of Brewer’s yeast could be used as an alternative pyrogen during antipyretic drug testing. Using the same methods as outlined for my second study, I therefore characterised the sickness responses and activation of inflammatory mediators associated with subcutaneous injection of two doses of zymosan (300 mg/kg and 30 mg/kg). My results show that zymosan dose-dependently induces fever, lethargy, anorexia and body mass stunting and that zymosan activates the same suite of inflammatory mediators as Brewer’s yeast albeit on a more moderate scale. Thus, zymosan could be used as a pyrogen for simulating fungal infections during antipyretic drug testing. In conclusion, the studies undertaken as part of my PhD have shown that among the methods and models currently recommended for use during antipyretic drug testing, rectal thermometry is associated with stress and hyperthermia which can potentially affect the accuracy and reliability of observations and conclusions drawn on the efficacy of test drugs. Additionally, at the recommended doses, Brewer’s yeast induces fever and sickness behaviours albeit with undesirable animal welfare challenges such as hypothermia, excessive inflammation and a lengthy sickness response due to the development of an abscess. However, zymosan is suitable for use as alternative to Brewer’s yeast as it is capable of inducing fever, sickness behaviours and inflammation of a moderate magnitude, which would allow pharmacological interventions without inducing animal suffering related to an excessive and prolonged inflammation.
A Thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, Johannesburg 2018
Keywords: Emergencies; Emergency Medicine